Becoming agile : how the SEAM approach to management builds adaptability /: how the SEAM approach to management builds adaptability. ([2015]) - Worley, Christopher G; Zardet, Véronique; (Professor of management), Bonnet, Marc; Savall, Amandine
No abstract available